Does Senior High School Strand Matter in Nursing Students’ Academic Self-Regulated Learning and Academic Performance? - Malaga, Xerxes G.; Oducado, Ryan Michael F. (South East Asia Nursing Research, 2021)
The Philippines recently adopted the K to 12 program in basic education. Under this program, students can choose their track and strand relative to their interests or career choices when they reach senior high school. However, issues surfaced when the K to 12 graduates were admitted to the college courses not aligned with the strand they have completed. This cross-sectional study was conducted to determine the difference in the academic self-regulated learning and performance of the STEM (Science and Technology, Engineering, and Mathematics) and non-STEM graduates in senior high school among freshmen nursing students in a city-subsidized college in the Philippines. The Academic Self-Regulation Learning Scale and grades of students in the first semester were used and analyzed in this study. Results showed that there was a significant difference in the academic self-regulated learning (p=0.045) and academic performance (p=0.000) of freshmen nursing students when grouped according to their senior high school strand.  The STEM graduates had significantly higher academic self-regulated learning and academic performance than the non-STEM completers. Unfortunately, no significant relationship was established between academic self-regulated learning and academic performance (p=0.559). Students who are graduates of the STEM strand from senior high school appear to be better prepared to take up the nursing course. Colleges of nursing may consider the academic strand of students in senior high school when admitting students in the nursing program.